2016
DOI: 10.1016/j.enbuild.2016.09.052
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of efficient water heating options for an all-electric single family residence in a mixed-humid climate

Abstract: An evaluation of a variety of efficient water heating strategies for an all-electric single family home located in a mixed-humid climate is conducted using numerical modeling. The strategies considered include various combinations of solar thermal, heat pump, and electric resistance water heaters. The numerical model used in the study is first validated against a year of field data obtained on a dual-tank system with a solar thermal preheat tank feeding a heat pump water heater that serves as a backup. Modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…The COP coefficient during work of the heat pump in the experiment was quite high: from 2.23 to 4.50. Similar achievements were presented by the other authors [1][2][3]5]. The results show that highest efficiency of the heating pump, determined as the COP coefficient, depends on the external air temperature.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The COP coefficient during work of the heat pump in the experiment was quite high: from 2.23 to 4.50. Similar achievements were presented by the other authors [1][2][3]5]. The results show that highest efficiency of the heating pump, determined as the COP coefficient, depends on the external air temperature.…”
Section: Resultssupporting
confidence: 89%
“…Traditional heating systems have an efficiency of 0.5 to 0.99 with respect to primary energy of fuel [3,4]. Heat pumps are strongly recommended for house heating due to their effectiveness, and are treated as renewable energy source [4,5]. The heat pumps might be on-line controlled and the data are registered, many parameters might be optimized by the user [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…With regards to water use, the home has energy and water efficient appliances and fixtures, and a PEXmanifold "home-run" plumbing system. Studies are being conducted on thermal losses from plumbing(Ullah and Healy, 2016), thermal performance of water heating systems(Ullah and Healy, 2016;Balke, et al, 2016), and premise plumbing microbial and chemical water quality. More information about the NZERTF, including recent publications and research results, can be found at https://www.nist.gov/el/net-zero-energy-residential-test-facility.Whirlpool Corporation and Purdue University transformed an existing 1920's home in West Lafayette, IN into a research facility called the Retrofit Net-zero: Energy, Water, and Waste (ReNEWW) house (https://www.whirlpoolcorp.com/reneww-house/).…”
mentioning
confidence: 99%
“…Microglia dysregulation has been associated with neuroinflammation induced by the binding of CX3CL1, IL-6, TGF-β and other cytokines 40 - 42 . Activated glial cells then initiate intracellular signaling cascades to trigger the release of both pro- and anti-inflammatory signals 43 . In this study, we identified several miRNAs in the circulation of IS patients that contribute to these mechanisms.…”
Section: Discussionmentioning
confidence: 99%